An Experimental Test of Deviant Modeling. (July 2016) - Gallupe, Owen; Nguyen, Holly; Bouchard, Martin; Schulenberg, Jennifer L.; Chenier, Allison; Cook, Katie D.
Objectives: Test the effect of deviant peer modeling on theft as conditioned by verbal support for theft and number of deviant models. Methods: Two related randomized experiments in which participants were given a chance to steal a gift card (ostensibly worth CAN$15) from the table in front of them. Each experiment had a control group, a verbal prompting group in which confederate(s) endorsed stealing, a behavioral modeling group in which confederate(s) committed theft, and a verbal prompting plus behavioral modeling group in which confederate(s) did both. The first experiment used one confederate; the second experiment used two. The pooled sample consisted of 335 undergraduate students. Results: Participants in the verbal prompting plus behavioral modeling group were most likely to steal followed by the behavioral modeling group. Interestingly, behavioral modeling was only influential when two confederates were present. There were no thefts in either the control or verbal prompting groups regardless of the number of confederates. Conclusions: Behavioral modeling appears to be the key mechanism, though verbal support can strengthen the effect of behavioral modeling.